Wages in Employment Relations in the Tourism Sector in Yogyakarta in Justice Perspective - Shalihah, Fithriatus; Alviah, Siti; Shob’ron, Imtikhan Anas (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2023)
The tourism sector in Indonesia plays a significant role in the country's foreign exchange income. Optimizing this sector is seen as a way to stimulate various economic segments after the Covid-19 pandemic. However, the workers in this industry face multiple challenges in their employment relationships. Issues such as sub-minimum wages and excessive working hours are prevalent among workers in the hotel, restaurant, and travel agency domains. These problems indicate systemic obstacles within the industry. This study focuses on the Special Region of Yogyakarta and examines the legal intricacies within the employment relationships of its tourism sector. Specifically, it explores the Culinary and Cultural Services Sector associated with the Remains of the Tombs of Kings. The primary goal is to clarify the nuances of justice within employment relationships and scrutinize the alignment of rights for culinary service workers and royal grave attendants with Indonesian law or the presence of justifiable legal reasons for deviations. The research methodology involves comprehensive data collection through stakeholder interviews, summarizing diverse challenges in the field. Findings underscore persistent discrepancies, notably within certain restaurants that violate the stipulated minimum wage as per the Indonesian Job Creation Law through fixed-term or indefinite-term work agreements. On the other hand, the employment relationship of Abdi Dalem workers, safeguarding Kings' tombs, aligns with labor laws due to their casual daily worker status, justified by an intermittent work schedule that exceeds legal provisions. In conclusion, this research provides a nuanced understanding of the existing issues within the employment relationships of the tourism sector. It sheds light on both legal infringements and instances where deviations are substantiated by explicit legal rationales.